Weight bias among students and employees in university settings: an exploratory study - Léonie Sohier; Claudia Mc Brearty; Stéphanie LeBlanc; Dominic J. Chartrand; Audrey St-Laurent; Schohraya Spahis; Léonel Philibert; Inès Auclair Mangliar; Marie-Pierre Gagnon-Girouard; Clara Lakritz; Sylvain Iceta (BMC Public Health)
Abstract Background Weight bias and stigmatization are highly prevalent in modern society, especially in educational settings, such as universities. Despite extensive documentation of the adverse consequences on students’ daily functioning and psychological health, there is limited literature regarding factors associated with weight bias and its extent in Quebec universities. Objectives This exploratory study aims to assess the prevalence of weight bias and experiences of weight-related stigmatization, as well as to examine their associations with gender, psychological health problems, and status (students or employees) in a college environment in the province of Quebec. Methods Participants were recruited via their university emails. A total of 292 students and 129 university employees participated in an online survey distributed via the secure REDCap platform. The following data was collected: sociodemographic information, status (students or employees), body weight, experiences of stigma, and prejudice towards people living with a higher weight (Fat Phobia Scale; FPS). Results Approximately half of the respondents reported experiencing weight-related stigma (44.7%), and half indicated holding prejudice towards overweight people (51.1%), with a moderate rate of bias according to the FPS (3.25). Experience of weight-related stigma was found to be associated with gender (X 2 = 7.88, p = 0.019), and a higher prevalence of psychological health problems (X 2 = 9.41, p = 0.002), while having prejudice was associated with gender, with men scoring higher at the FPS (F = 7.64, p = 0.006), but not with the status (student or employee). The regression model identified significant effects of status [F(4, 347) = 2.856, p = 0.005] and the interaction between gender and status [F(4, 347) = -2.326, p = 0.021] on the FPS scores. Conclusions Various factors are associated with the experience of weight bias and stigmatization towards people with higher weight in the college population. Campaigns to prevent and reduce weight-related bias should be aimed specifically at staff members as well as students. Future research should examine weight bias internalization as a mediator between self-perceived weight and prejudice.